Childhood anemia in populations residing at different geographical altitudes of Arequipa, Peru: associated maternal factors - Munoz-del-Carpio-Toia, Agueda (2023)
Objective: Determine the relationship between socio-demographic characteristics, knowledge, and good practices in anemic children and anemic child healthcare in Arequipa, Peru. Study design:  This is a cross-sectional survey. Participants were asked about their knowledge of childhood anemia, practices related to caring for anemic children, and adherence to treatment. Methods: This is a descriptive, transversal, relational field study. Three hundred mothers with anemic children were interviewed, from six districts of Arequipa, distributed at different geographic altitudes: medium-altitude, great-altitude, and sea level. Studied variables were related to socio-demographic factors, level of knowledge, anemic children care-related practices, and treatment adherence.  Results: 77.3% of children had mild anemia, 21.6% moderate, and 1% severe anemia. The number of children and disease severity were significantly related (p<0.05) to knowledge about anemia. Knowledge about anemia, living area, and geographic altitude were significantly correlated (p<0.05) with good practices in child anemia. Conclusion: the prevalence of anemia in the region of Arequipa is incremented by socio-economic factors, mother’s education, number of children, altitude, and geographic zone. The implementation of mother-centered educational programs by the government is necessary. In this sense, the results suggest further studies in social representations to understand, analyze and deepen the knowledge of the subject.